Biomimetics: Restoration of Impact Damage in Polymers via a Hybrid Microcapsule–Microvascular Self‐Healing System (Adv. Funct. Mater. 2/2018). (8th January 2018) - Gergely, Ryan C. R.; Santa Cruz, Windy A.; Krull, Brett P.; Pruitt, Emmy L.; Wang, Jonathan; Sottos, Nancy R.; White, Scott R.
Abstract : In article number1704197, Scott R. White and co‐workers present a novel hybrid system that incorporates both microcapsules and microvascular delivery for the restoration of impact puncture damage. The image shows the damage with radiating microcracks repaired by ruptured embedded microcapsules (green), and the central puncture being restored with two‐stage healing agents (blue and red).